Pengaruh Model Pembelajaran STEAM terhadap Kemampuan Sains dan Numerasi Siswa Madrasah Ibtidaiyah - Budiyono, Aan; Luthfi, Amir; Witarsa, Ramdhan (Universitas Negeri Makassar, 2023)
: Science and numeracy skills are part of basic literacy skills that must be mastered by students. Both of these abilities are included in the ability to think intermediate to high-level thinking skills. Students must begin to be invited to think at a medium to high level so that these two abilities can develop and improve optimally. This research aims to measure how much influence the learning models of science, technology, engineering, arts, and mathematics have on the science and numeracy skills of madrasah ibtidaiyah students. The method used in this research is a quasi-experimental method. The data collection technique used was a student's science and numeracy ability test. The research instrument used was a student's science and numeracy test sheet. The results of the research show that the learning models of science, technology, engineering, arts, and mathematics have a significant effect on the science and numeracy abilities of fifth grade students of Madrasah Ibtidaiyah. Therefore, this research can be a reference in applying science, technology, engineering, arts, and mathematics learning models that can affect students' science and numeracy skills.